Analisis Keruangan Kesesuaian Lahan untuk Permukiman di Kabupaten Bandung dan Bandung Barat - Rina Marina Masri (Forum Geografi, 2012)
The objectives of research are: to evaluate land suitability for housing based on soil characteristics; and to propose policy on the sustainable housing development in Bandung and West Land Bandung District. The method used in the spatial analysis is descriptive method based on several i.e. on data description of a case, circumstances, attitudes, relationships or a system of thought that became the object of research. The result of research as follows: 41.76% at fine zone residential lands, 44.81% at moderate zone residential good lands. Result of analysis give alternatives policies as set up the standardization the building coverage ratio, limited the conservation area to residential lands and others, increasing the conservation funding for decreasing natural accident disaster as flood, landslides etc.